Agency costs, corporate governance mechanisms and performance of public listed family firms in Malaysia - H. Ibrahim; F. A. Samad (South African Journal of Business Management, 2011)
We compare corporate governance and performance between family and non-family ownership of public listed companies in Malaysia from 1999 through 2005 measured by Tobin's Q and ROA. We also examine the governance mechanisms as a tool in monitoring agency costs based on asset utilization ratio and expense ratio as proxy for agency costs. We find that on average firm value is lower in family firms than non-family firms, while board size, independent director and duality have a significant impact on firm performance in family firms as compared to non-family firms. We also find that these governance mechanisms have significant impact on agency costs for both family and non-family firms.
Keywords: 650